كۆچی ئه‌قڵه‌كان: (چه‌مك و هۆكاره‌ پاڵنه‌ر و كه‌مه‌ندكێشه‌كانی) - مجید, د. په‌یمان عبدالقادر; احمد, م. عمر علی (Sulaimani Journal for Humanities, 2023)
This research is an attempt to define the concept of brain drain and mention the reasons or motives that led to the migration of people with brains from their countries to other countries. At the same time, it is an attempt to present the factors that made developed and developed countries to attract people with scientific and mental qualifications to their countries, in addition to that this study is an attempt to identify the concept of brain drain and scientific theories. The nature of the research necessitated that we rely on the analytical descriptive approach due to its suitability and consistency with the results that the research seeks to reach. The brain drain is a theoretical analysis, in addition to mentioning the historical roots of this phenomenon in Iraq in general and the Kurdistan region in particular. In conclusion, the researcher came to the conclusion that the British were the ones who invented the concept of brain drain and they have the precedence in this issue, in order to express the extent of the damage they suffered as a result of the migration of these scientists, engineers and doctors who left the country and went to other countries, especially America. Also, the phenomenon of brain drain is not new, but after broadening the horizons of the issue of globalization and its widespread spread significantly, and the progress and development that the world has witnessed recently in the field of technology, this phenomenon has taken one path, as the phenomenon of brain drain has become specialized in the migration of people with competencies and minds from developing and poor country. To Western and European countries where life is completely different from that. The way of life, respect for human rights, applicable laws, and the way of daily life had a great impact on the migration of people of intellect and people with different competencies and their acquisition by those countries.